Popularization of health in Polish philately - Marek Smoła (University of Applied Sciences in Tarnow, Poland, 2023)
The promotion of health and its protection is carried out in various ways. Philately, collecting, and professional knowledge, not limited to stamps, also utilize objects that were once very popular and commonly used in correspondence - postcards. The article compiles information on the issuance of postcards by the Polish Post from 1919 to 2022, related to the broadly understood issue of health. There is room here for figures such as doctors, researchers, and discoverers of modern methods and phenomena, for the celebrations of institutions dedicated to protecting health, for important events (congresses, first surgeries and procedures), and for social phenomena. Referring to them is intended to raise awareness and expand human knowledge, for example in the field of prevention.